Retrospective analysis of chest x-ray of patients from eastern Uttar Pradeshpresenting in Radiology department ofHind Institute Medical Sciences, Barabanki Uttar Pradesh - Khare, Rekha; Khare, A.K. (International Journal of Medical Research and Review, 2019)
Introduction: Chest Xray is one of the most frequently asked radiological examination in patients with heart or lung problems in general medical practice. There are many studies on correlation of CXR findings and other tools of investigations like CT scan, MRI and laboratory investigations like spirometry and sputum examinations etc. The present study aims at establishing a possible correlation in rural population of Eastern Uttar Pradesh. Methods: We have done a cross sectional study in a period of six months including 2500 patients coming for CXR. Patients were followed up to a point where radiological diagnosis was confirmed or otherwise after other investigations and clinical response. Results: There was fairly good correlation in patients with COPD (73.15%), tuberculosis (85.8%), interstitial lung disease (63.9%) and congestive heart failure (68.6%). Conclusion: We conclude that CXR is tool of reasonable sensitivity however there is sizeable possibility of false positive and negative cases.